The Development of Digital Indonesian Folklore as An Instrument for Fostering Character in Literature Learning - I Wayan Numertayasa; I Nengah Sueca; Ni Made Kemba Rianti (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2026)
This study aims to develop a prototype of digital folklore for character building in literature education. This study employs a Research and Development (R&D) approach based on Borg and Gall’s model. The model is adapted and simplified into several stages, focusing on product development, expert validation, and product revision based on expert feedback, and employs two data analysis techniques: qualitative descriptive analysis and descriptive statistical analysis. The findings reveal that literature learning requires digital folklore to shape students' character effectively. Furthermore, the development of digital folklore for character building in literature education is deemed valid. Thus, it can be concluded that digital folklore is beneficial for literature learning and essential for character development. It is therefore recommended that teachers incorporate digital folklore into literature lessons to support character building. Additionally, further research is encouraged to develop existing Indonesian folklore.